Group A, G and C Î²-hemolytic Streptococci - K.L, Shobha; N., Kusumakshi; Prasad, Vishnu; L., Ramachandra (International Journal of Medicine, 2015)
Group A Streptococcus (GAS) is the most common causative agent of sore throat, pharyngitis, skin infections, rheumatic fever (RF), rheumatoid heart disease (RHD) and glomerulonephritis in young adults. Group G and C streptococcal species are also known to cause complications like acute rheumatic fever and rheumatic heart disease. Isolation of these from the throat could be a warning signal so that the further complications can be prevented. Estimation of prevalence could help clinicians to make informed decisions regarding diagnostic testing of children with symptoms of sore throat and pharyngitis. M protein both GAS and GGS/GCS share in many virulence factors that contribute to virulence, some of which act as collagen binding adhesins that facilitate acute infection. Both GAS and GGS/GCS can cause similar spectrum of disease symptoms. The sequenced M Protein provides a view into the genetic elements responsible for diversity in the species. emm types historically associated with RF are rarely seen in India. The epidemiologic picture of streptococci in India shows some of the serotypes are more common with in a population in different geographical area.